Numerical simulation of performance and emission of marine diesel engine under different gravity conditions. (July 2020) - Lu, Xiuwei; Geng, Peng
A computational fluid dynamics model of the marine diesel engine was established and validated, and the simulation studies were carried out using this model. Different gravity conditions were set in the computational fluid dynamics model to investigate their effect on marine diesel emissions and performance. By comparing the simulation results under different basic grid sizes, 1.2 mm was selected as the basic grid size of the computational fluid dynamics model. The model uses the experimental data including cylinder pressure, heat release rate, and nitrogen oxides (NO x ) emissions to calibrate and validate the model. The simulation results are very close to the experimental data, and slight errors are also within the allowable range. In particular, when considering the heat transfer of the combustion chamber wall, the simulation results of the heat release rate are closer to the experimental data. The simulation results show that gravity has a slight effect on cylinder pressure and heat release rate, and has a certain degree of effect on fuel spray and atomization. The penetration length of the fuel is proportional to the gravity, and the maximum deviation of the Sauter mean diameter of the droplet is 25.74%. The spray and atomization process of fuel directly affects combustion and emissions. The maximum deviation of NO x emissions is 6.03%, which is reduced from 7.46 to 7.01 g/kW·h. Finally, the three-dimensional simulation results of temperature, equivalence ratio, and NO x emission of different crank angles under different gravity conditions are compared.